Negative electrode material for secondary battery, negative electrode and secondary battery
Patent Information
- Application Number
- JP2022206419
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-30
- Filing Date
- 2022-12-23
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2041-08-25
AI Technical Summary
【0041】 本発明による二次電池用負極材は、シリコン酸化物、アルカリ金属とアルカリ土類金属およびポスト遷移金属からなる群から選択される一つ以上のドーピング元素とシリコンとの複合酸化物、またはこれらの混合物を含有するマトリックスおよびマトリックスに分散含浸されており、残留圧縮応力を有するナノ粒子状のシリコンによって向上した機械的物性、電気化学的特性を有し、特に、高い放電容量とともにシリコン系負極材が備えられた二次電池の実商用化が可能な水準の容量維持率を有する利点がある。
Smart Images

Figure 0007633226000004 
Figure 0007633226000005 
Figure 0007633226000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an anode material for a secondary battery, and more particularly to an anode material for a secondary battery having improved capacity, initial efficiency and cycle characteristics. [Background technology]
[0002] Demand for long-life, high-energy density and high-power density secondary batteries continues to increase in various industrial sectors, including electronic products, electric / hybrid cars, and aerospace / drones.
[0003] The typical anode material used commercially is graphite, whose theoretical maximum capacity is only 372mAh / g. Therefore, in order to realize secondary batteries with high energy density, research is being conducted to use chalcogen-based materials such as sulfur (maximum capacity 1675mAh / g), silicon-based materials such as silicon (maximum capacity 4200mAh / g) and silicon oxide (maximum capacity 1500mAh / g), and transition metal oxides as secondary battery anode materials, and among the various materials, silicon-based anode materials are attracting the most attention.
[0004] However, when particulate silicon is used as the anode material, repeated charge-discharge cycling causes the battery characteristics to deteriorate rapidly due to insulation, particle detachment, and increased contact resistance caused by large volume changes in silicon, resulting in the battery losing its function within 100 cycles.In the case of silicon oxide, irreversible products such as lithium silicate and lithium oxide cause lithium loss, resulting in a rapid decrease in the initial charge-discharge efficiency.
[0005] To solve these problems with silicon-based anode materials, various technologies have been proposed, including nano-silicon in the form of wires and then compounding them with carbon materials, doping silicon oxide with different metals to form a compound oxide phase, or pre-lithiating silicon oxide. However, initial charge / discharge efficiency, cycle characteristics, and high-rate characteristics are still degraded, making commercialization difficult. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Korean Patent Publication No. 10-2020-0065514 [Patent Document 2] Korean Patent Publication No. 10-2015-0045336 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide an anode material for a silicon-based secondary battery having a high battery capacity, improved initial reversible efficiency, and stable cycle characteristics. [Means for solving the problem]
[0008] According to one embodiment of the present invention, the negative electrode material for a secondary battery may include a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof, and silicon nanoparticles dispersed and embedded in the matrix and having a residual compressive stress.
[0009] According to another embodiment of the present invention, there is provided a negative electrode material for a secondary battery, which comprises a matrix containing a silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and may satisfy the following formula 1:
[0010] (Formula 1) 1 <WN(Si) / WN(ref)
[0011] In Equation 1, WN(ref) is the central wavenumber of the Raman peak of bulk single crystal silicon, and WN(Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the negative electrode material.
[0012] In the negative electrode material for secondary batteries according to one embodiment of the present invention, the difference between WN(Si) and WN(ref) is 0.1 cm -1 It could be more than that.
[0013] In the negative electrode material for a secondary battery according to one embodiment of the present invention, the full width at half maximum (FWHM) of the Raman peak of the nanoparticle silicon contained in the negative electrode material may be greater than the FWHM of the Raman peak of bulk single crystal silicon.
[0014] In the negative electrode material for a secondary battery according to one embodiment of the present invention, the FWHM of the Raman peak of the nanoparticle-shaped silicon contained in the negative electrode material is 4 to 20 cm -1 It could be.
[0015] In the negative electrode material for secondary batteries according to one embodiment of the present invention, when a two-dimensional mapping analysis is performed based on the Raman signal of silicon, the difference between the maximum and minimum shifts defined by the following formula 2 is 5 cm under the following mapping conditions: -1 It can be the following: Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, irradiation time = 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 0.1 cm -1 , mapping size = 14 μm × 14 μm
[0016] (Formula 2) Deviation=WN i (Si)-WN(ref)
[0017] In formula 2, WN(ref) is the same as that in formula 1, and WN i(Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the negative electrode material in one pixel, which is a unit analysis area during mapping analysis.
[0018] According to yet another aspect of the present invention, there is provided a negative electrode material for a secondary battery, comprising a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and the negative electrode material may have a hardness of 4.0 GPa or more and a Young's modulus of elasticity of 40 MPa or more in a nanoindentation test.
[0019] According to yet another aspect of the present invention, there is provided a negative electrode material for a secondary battery in the form of particles including a matrix containing a silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and the compressive strength of the particles may be 100 MPa or more.
[0020] According to yet another embodiment of the present invention, a negative electrode material for a secondary battery includes a matrix containing silicon (Si), one or more doping elements (D) selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, and oxygen (O) based on elemental components, and silicon nanoparticles dispersed and impregnated in the matrix, and has a composition uniformity that satisfies the following formula 3:
[0021] (Formula 3) B / A≦0.30
[0022] In Equation 3, A and B are the average (A) and standard deviation (B) of the content (wt%) of the doping element measured at 100 random points on a cross section crossing the center of the negative electrode material.
[0023] In the negative electrode material for secondary batteries according to one embodiment of the present invention, based on the compound components, the matrix may include silicon oxide and a composite oxide of the doping element and silicon.
[0024] According to yet another embodiment of the present invention, there is provided an anode material for a secondary battery, comprising: a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of silicon oxide, alkali metals, alkaline earth metals, and post transition metals, or a mixture thereof; and silicon nanoparticles dispersed and impregnated in the matrix, wherein a volume change of the anode active material layer during charging up to 0.005 V is within 60% based on a composition of 80% by weight of an active material including the anode material, 10% by weight of a conductive material, and 10% by weight of a binder.
[0025] According to yet another aspect of the present invention, there is provided a negative electrode material for a secondary battery, comprising a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and the negative electrode material is characterized in that, in a dQ / dV graph obtained by a charge-discharge test under the following charge-discharge cycle conditions using a half cell having a lithium foil as a counter electrode, Li 3.75 There is a lithium insertion peak corresponding to the Si reaction, and the discharge capacity in the first charge / discharge cycle is 1200 mAh / g or more.
[0026] Charge / discharge cycle conditions: CC / CV, cut-off voltage 0.005V~1.0V, 0.5C-rate
[0027] According to yet another aspect of the present invention, there is provided a negative electrode material for a secondary battery, which comprises a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and satisfies Equation 4 during a charge-discharge test under the following charge-discharge cycle conditions using a half cell having a lithium foil counter electrode.
[0028] Charge / discharge cycle conditions: CC / CV, cut-off voltage 0.005V~1.0V, 0.5C-rate
[0029] (Formula 4) 95%≦C50 / C1*100
[0030] In Equation 4, C1 is the discharge capacity (mAh / g) at the first charge / discharge cycle, and C50 is the discharge capacity at the 50th charge / discharge cycle.
[0031] In the negative electrode material for a secondary battery according to one embodiment of the present invention, C50 may be 1200 mAh / g or more.
[0032] In the negative electrode material for a secondary battery according to one embodiment of the present invention, the silicon nanoparticles may have an average diameter of 2 to 30 nm.
[0033] In the negative electrode material for secondary batteries according to one embodiment of the present invention, the interface between the silicon nanoparticles and the matrix may be a coherent interface.
[0034] In the negative electrode material for a secondary battery according to an embodiment of the present invention, the matrix may further include a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals.
[0035] In the negative electrode material for secondary batteries according to an embodiment of the present invention, the doping element may be one or more selected from lithium (Li), sodium (Na), potassium (K), aluminum (Al), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba).
[0036] In the negative electrode material for a secondary battery according to an embodiment of the present invention, the composite oxide may include a crystalline material.
[0037] In the negative electrode material for a secondary battery according to one embodiment of the present invention, the negative electrode material has an average diameter of 10 0 μm order ~ 10 1 It may be in the form of particles on the order of μm.
[0038] In the negative electrode material for a secondary battery according to an embodiment of the present invention, the negative electrode material may further include a coating layer containing carbon.
[0039] The present invention includes a negative electrode comprising the above-mentioned negative electrode material for a secondary battery.
[0040] The present invention includes a secondary battery including the above-described negative electrode. Effect of the Invention
[0041] The negative electrode material for secondary batteries according to the present invention is a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and is dispersed and impregnated in the matrix. The matrix has improved mechanical properties and electrochemical properties due to nanoparticle-like silicon having residual compressive stress, and is particularly advantageous in that it has a high discharge capacity as well as a capacity retention rate at a level that allows for practical commercialization of secondary batteries equipped with the silicon-based negative electrode material. [Brief description of the drawings]
[0042] [Figure 1] FIG. 2 is a diagram illustrating an EDS line profile of Mg in a cross section of a negative electrode material manufactured according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a graph showing a Raman spectrum of a negative electrode material prepared according to an embodiment of the present invention. [Diagram 3] FIG. 1 illustrates two-dimensional mapping results based on Raman signals of silicon in an anode material manufactured according to one embodiment of the present invention. [Figure 4] FIG. 4 is a graph showing the strength and elastic modulus of a negative electrode material manufactured according to an embodiment of the present invention. [Diagram 5] 1 is a graph showing the battery capacity measured according to the charge / discharge cycle of a half cell including a negative electrode including a negative electrode material prepared according to an embodiment of the present invention. [Figure 6] 1 is a high-magnification transmission electron microscope photograph of a negative electrode material manufactured according to an embodiment of the present invention. [Figure 7] 1 is a high-magnification transmission electron microscope photograph of a matrix of a negative electrode material manufactured according to an embodiment of the present invention, and a selected area diffraction pattern (SADP) of the matrix. [Figure 8] 1 is a scanning electron microscope photograph showing a cross section and thickness of a negative electrode including a negative electrode material manufactured according to one embodiment of the present invention before and after lithiation; [Figure 9] FIG. 4 is a graph showing the particle size distribution of a negative electrode powder produced according to an embodiment of the present invention. [Figure 10] 4 is a dQ / dV graph of a half cell including a negative electrode including a negative electrode material according to one embodiment of the present invention. [Figure 11] FIG. 2 is a diagram showing a selected area diffraction pattern (SADP) of a negative electrode material manufactured according to an embodiment of the present invention in a charged state. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0043] Hereinafter, the negative electrode material for secondary batteries according to the present invention will be described in detail with reference to the accompanying drawings. The drawings disclosed below are provided as examples to fully convey the concept of the present invention to those skilled in the art. Therefore, the present invention is not limited to the drawings presented below, and may be embodied in other forms, and the drawings presented below may be exaggerated to clarify the concept of the present invention. In this case, unless otherwise defined, the technical and scientific terms used have the meanings that are commonly understood by those having ordinary skill in the art to which the present invention belongs, and descriptions of known functions and configurations that may obscure the gist of the present invention in the following description and the accompanying drawings are omitted.
[0044] Also, as used in the specification and the appended claims, the singular forms "a," "an," and "the" are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0045] In this specification and the appended claims, the terms first, second, etc. are not meant to be limiting but are used to distinguish one element from another element.
[0046] In this specification and the appended claims, the terms "comprise" and "have" mean the presence of the features or components described in the specification, and do not preclude the possibility that one or more other features or components may also be added, unless specifically limited.
[0047] In this specification and the appended claims, when a part such as a film (layer), region, component, etc. is said to be on or above another part, this includes not only the case where it is directly on top of and in contact with the other part, but also the case where there is another film (layer), another region, another component, etc. interposed therebetween.
[0048] The applicant found that in a silicon-based anode material in which silicon and silicon-based oxide are composited, the mechanical and electrochemical properties of the anode material are significantly affected by the residual stress of silicon contained in the anode material. As a result of repeated research based on this discovery, the applicant found that when silicon is dispersed in the form of nanoparticles in a silicon-based oxide matrix and has residual compressive stress, the mechanical and electrochemical properties of the anode material are significantly improved, and thus the present invention was completed.
[0049] Therefore, the negative electrode material of the present invention based on the above-mentioned discovery exhibits mechanical and electrochemical properties that cannot be obtained from conventional silicon-based negative electrode materials due to the bond between the silicon dispersed in nanoparticles and having residual compressive stress and the matrix, and therefore the present invention includes various aspects based on the properties of the silicon-based negative electrode material of the present invention.
[0050] In the present invention, the matrix may refer to a solid medium in which nanoparticle silicon is dispersed, or may refer to a material that forms a continuous phase for silicon nanoparticles that are a dispersed phase in the negative electrode material. In the present invention, the matrix may refer to a material (or materials) other than metallic silicon (Si) in the negative electrode material.
[0051] In the present invention, nanoparticles are generally defined as nanoparticles having a size (diameter) of 10 0 Nanometer order ~ 10 2 Particles on the nanometer order can mean particles having a diameter substantially equal to or less than 500 nm, specifically equal to or less than 200 nm, more specifically equal to or less than 100 nm, and even more specifically equal to or less than 50 nm.
[0052] In the present invention, the negative electrode material for a secondary battery includes, but is not necessarily limited to, a negative electrode material for a lithium secondary battery. The negative electrode material of the present invention can be used as an active material for secondary batteries such as sodium batteries, aluminum batteries, magnesium batteries, calcium batteries, and zinc batteries, and can also be used in other energy storage / generation devices in which conventional silicon-based materials are used, such as supercapacitors, dye-sensitized solar cells, and fuel cells.
[0053] The negative electrode material for a secondary battery according to one embodiment (I) of the present invention includes a matrix containing a silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and satisfies the following formula 1.
[0054] (Formula 1) 1 <WN(Si) / WN(ref)
[0055] In Equation 1, WN(ref) is the central wavenumber of the Raman peak of bulk single crystal silicon, and WN(Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the negative electrode material.
[0056] In Equation 1, the ratio of the central wavenumber of the Raman peak of bulk single crystal silicon to the central wavenumber of the Raman peak of nanoparticle-shaped silicon contained in the negative electrode material is a parameter indicating the type and magnitude of stress (residual stress) remaining in the silicon nanoparticles dispersed and impregnated in the matrix.
[0057] In formula 1, the term bulk single crystal silicon should be interpreted as meaning silicon having a size that substantially exhibits the physical properties of bulk single crystal silicon. In terms of providing a clear comparison standard and ensuring ease of purchase, bulk single crystal silicon may mean a single crystal silicon wafer having a thickness of the sub-mm order, specifically, a thickness of 0.4 to 0.7 mm.
[0058] In formula 1, WN(Si) / WN(ref) exceeding 1 means that the central wavenumber of the Raman peak of the nanoparticle silicon contained in the negative electrode material shifts to a longer wavenumber (shorter wavelength of Raman scattered light) compared to bulk single crystal silicon, and means that the nanoparticle silicon has residual compressive stress.
[0059] In Equation 1, for bulk single crystal silicon and nanoparticle silicon, the Raman peak of silicon is 500 to 540 cm in the Raman spectrum of silicon. -1 In the region of 510-530 cm -1 in the region of 515-528 cm -1 The central wavenumber of the peak, i.e., the wavenumber corresponding to the center of the peak, may refer to the wavenumber having the maximum intensity value in the peak. In this case, when two or more Raman peaks are present in the above-mentioned Raman shift region, the peak with the highest intensity may correspond to the Raman peak of silicon of formula 1, and when two or more Raman peaks overlap each other to show a birod shape, the wavenumber having the maximum intensity value in the birod with the highest intensity may correspond to the central wavenumber of the peak.
[0060] The difference between WN(Si) and WN(ref) (WN(Si)-WN(ref)) is a parameter that directly indicates the magnitude of the residual compressive stress of the silicon nanoparticle. -1 More than 0.2cm -1 More than 0.3cm -1 More than 0.4cm -1 More than 0.5cm -1 More than 0.6cm -1 More than 0.7cm -1 More than 0.8cm -1 More than 0.9cm -1 More than 1.0cm -1 Over 1.1cm -1 More than 1.2cm -1 Over 1.3cm -1 Over 1.4cm -1 Over 1.5cm-1 More than 1.6cm -1 Over 1.7cm -1 More than 1.8cm -1 More than 1.9cm -1 Over 2.0cm -1 Over 2.1cm -1 More than 2.2cm -1 Over 2.3cm -1 Over 2.4cm -1 Over 2.5cm -1 More than 2.6cm -1 Over 2.7cm -1 More than 2.8cm -1 More than 2.9cm -1 3.0cm or more -1 Over 3.1cm -1 More than 3.2cm -1 Over 3.3cm -1 Over 3.4cm -1 Over 3.5cm -1 More than 3.6cm -1 Over 3.7cm -1 More than 3.8cm -1 More than 3.9cm -1 or more than 4.0cm -1 It can be more than 6.0 cm. -1 The actual value is 5.5cm. -1 It can be the following:
[0061] In addition to or independently of the difference between the central wavelengths of the Raman peaks of the bulk single crystal silicon and the nanoparticle silicon contained in the anode material, the FWHM of the Raman peak of the nanoparticle silicon contained in the anode material may be greater than the FWHM of the Raman peak of the bulk single crystal silicon. The greater FWHM value relative to the bulk single crystal silicon may be due to the structure in which the silicon contained in the anode material is dispersed and impregnated in the matrix in the form of extremely fine particles. Specifically, the FWHM of the Raman peak of the nanoparticle silicon contained in the anode material is 4 to 20 cm. -1 , 6~20cm -1 , 6~18cm -1 , 6~16cm -1 , 8~20cm -1 , 8~18cm-1 , 8~16cm -1 , 10~20cm -1 , 10~18cm -1 , or 10-16cm -1 It may be, but is not necessarily limited to this.
[0062] In addition to this, or independently, the nanoparticle silicon contained in the negative electrode material is measured using the Raman spectrum of the silicon Raman peak (0 cm -1 ) as the standard on the Raman spectrum, +20 cm -1 Intensity (I1) at the position (wave number) and -20 cm -1 The intensities (I2) at the positions (wave numbers) of -20 cm can be significantly different from each other. -1 The intensity (I2) at the position (wave number) is +20 cm -1 At this point, "significantly different" may mean that the ratio of I2 / I1 is 1.20 or more. The asymmetric Raman peak of silicon (long tail in the short wavenumber direction) may also be due to the structure in which silicon nanoparticles having residual compressive stress are dispersed and impregnated in the matrix.
[0063] In addition, when the anode material is subjected to two-dimensional mapping analysis based on the Raman signal of silicon, the difference between the maximum and minimum shifts defined by the following formula 2 is 5 cm -1 It can be the following:
[0064] (Formula 2) Deviation=WN i (Si)-WN(ref)
[0065] In formula 2, WN(ref) is the same as that in formula 1, and WN i(Si) is the central wavenumber of the Raman peak of nanoparticle silicon contained in the anode material at one pixel, which is a unit analysis area during mapping analysis. In this case, in Equation 2, the shift can be calculated for each pixel only at the pixel where the silicon Raman signal is detected in the two-dimensional Raman map obtained by the two-dimensional mapping analysis, and it goes without saying that the maximum and minimum values refer to the maximum and minimum values of the shifts calculated by Equation 2.
[0066] Using the two-dimensional Raman map of silicon obtained by two-dimensional mapping analysis of the anode material based on the Raman signal of silicon as a reference, the difference between the maximum and minimum values of the central wavenumber shift value (shift) of the silicon peak relative to bulk single crystal silicon according to Equation 2 is an index showing the uniformity of the residual compressive stress of the silicon nanoparticles dispersed and impregnated in the anode material. The difference between the maximum and minimum values of the reference shift of the two-dimensional Raman map is 5.0 cm -1 Below, 4.5cm -1 Below, 4.0cm -1 Below, 3.5cm -1 Below, 3.0cm -1 Below, 2.5cm -1 Less than or equal to 1.0 cm -1 The following can be satisfied, and the difference between the maximum and minimum values is practically 0.1 cm. -1 More effectively, 0.5 cm -1 The difference between the maximum value and the minimum value means that most of the silicon nanoparticles, or substantially all of the silicon nanoparticles, contained in the negative electrode material have residual compressive stress, and further means that the magnitude of the compressive stress remaining in most of the silicon nanoparticles, or substantially all of the silicon nanoparticles, contained in the negative electrode material is substantially approximately the same.
[0067] Experimentally, the Raman spectrum of silicon contained in the anode material was measured at room temperature (20-25°C), under atmospheric pressure, with an excitation laser wavelength of 532 nm, a laser power of 0.5 mW, and a spectrometer resolution of 1 cm. -1 The measurement may be performed under the conditions of 1 g of negative electrode material and 15 s of detector exposure time.
[0068] Experimentally, two-dimensional Raman mapping of anode materials using silicon Raman signals was performed with the following conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time (exposure time per unit analysis area) 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm -1 , the mapping size may be 14 μm×14 μm, and the measurement may be performed at room temperature and atmospheric pressure.
[0069] The negative electrode material for secondary batteries according to another embodiment (II) of the present invention includes a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of silicon oxide, alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and may have a hardness of 4.0 GPa or more and a Young's modulus of elasticity of 40 MPa or more in a nanoindentation test. Hereinafter, in relation to the mechanical properties of the negative electrode material for secondary batteries, all properties are those at room temperature (20 to 25°C) unless a specific temperature is specified.
[0070] Nanoindentation testing can be performed in accordance with ASTM E2546, ISO 14577-1 E, ISO 14577-2 E, and ISO 14577-3 E. The elastic modulus E is, as is well known, calculated by the formula E = E * (1-ν 2 ), where E *is the elastic modulus of the indenter, and ν is the Poisson's ratio of the Berkovich indenter, which is assumed to be 0.3. The nanoindentation test using the Berkovich indenter may be performed under the conditions of a maximum load of 50 mN and a load application rate of 100 mN / min. The strength and elastic modulus measured by the nanoindentation test may be average values of physical properties obtained by performing a nanoindentation test in a matrix form of 5×5 to 25×25, with a separation distance between the indentation marks of the indenter being at least 10 μm or more. In this case, the negative electrode material sample to be subjected to the nanoindentation test may be prepared by mounting and polishing a bulk negative electrode material in a plate shape.
[0071] Specifically, the negative electrode material for secondary batteries has a strength (indentation strength) in a nanoindentation test of 4.0 GPa or more, 4.5 GPa or more, 5.0 GPa or more, 5.5 GPa or more, 6.0 GPa or more, 6.5 GPa or more, 7.0 GPa or more, 7.5 GPa or more, 8.0 GPa or more, 8.5 GPa or more, 9.0 GPa or more, 9.5 GPa or more, 10.0 GPa or more, 10.2 GPa or more, 10.4 GPa or more, 10.6 GPa or more, 10.8 GPa or more, 11.0 GPa or more, 11.2 GPa or more, 11.4 GPa or more, 11.6 GPa or more, 11.8 GPa or more, 12.0 GPa or more, 12.2 GPa or more, 12.4 GPa or more, 12.6 GPa or more, 12.8 GPa or more, or 13.0 GPa or more, and may be substantially 25.0 GPa or less, more substantially 20.0 GPa or less. In addition, the negative electrode material for secondary batteries may have an elastic modulus of 40 MPa or more, 45 MPa or more, 50 MPa or more, 55 MPa or more, 60 MPa or more, 65 MPa or more, 70 MPa or more, 75 MPa or more, 80 MPa or more, 85 MPa or more, 90 MPa or more, 92 MPa or more, 94 MPa or more, 96 MPa or more, 98 MPa or more, 100 MPa or more, 102 MPa or more, 104 MPa or more, 106 MPa or more, 108 MPa or more, 110 MPa or more, 112 MPa or more, 114 MPa or more, 116 MPa or more, 118 MPa or more, or 120 MPa or more, and may be substantially 250 MPa or less, more substantially 200 MPa or less.
[0072] The mechanical properties of the negative electrode material described above based on the nanoindentation test are properties that can be realized by the residual stress present in the negative electrode material, including the residual compressive stress of the nanoparticle silicon.
[0073] A negative electrode material with high strength and excellent elasticity means that the particulate negative electrode material is not physically damaged during the electrode manufacturing process, which is already established in the field of secondary batteries, including manufacturing a negative electrode material slurry, applying the slurry on a current collector, drying, and rolling (calendering). It also means that damage to the electrode (negative electrode) pore structure is prevented, ensuring stable and uniform contact with the electrolyte as designed.
[0074] The negative electrode material for secondary batteries according to another embodiment (III) of the present invention is in the form of particles including a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and the compressive strength (St) of the particles can be 100 MPa or more. As is well known, the compressive strength St of the particles can be expressed by the formula
number
[0075] Specifically, the particle compressive strength of the particulate negative electrode material for secondary batteries may be 100 MPa or more, 105 MPa or more, 110 MPa or more, 115 MPa or more, 120 MPa or more, 125 MPa or more, 130 MPa or more, 135 MPa or more, 140 MPa or more, 145 MPa or more, 150 MPa or more, 155 MPa or more, or 160 MPa or more, and may be substantially 250 MPa or less, more substantially 200 MPa or less.
[0076] The mechanical properties of the above-mentioned negative electrode material include the residual compressive stress of the silicon nanoparticles, and are physical properties that can be realized by the residual stress present in the negative electrode material. Furthermore, the mechanical strength and elasticity can be further improved by forming a stress field in the matrix surrounding the silicon nanoparticles with residual compressive stress due to the matching interface between the silicon nanoparticles and the matrix.
[0077] The negative electrode material for a secondary battery according to another embodiment (IV) of the present invention includes, based on elemental components, a matrix containing silicon (Si), one or more doping elements (D) selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, and oxygen (O), and silicon nanoparticles dispersed and impregnated in the matrix, and has a composition uniformity that satisfies the following formula 3.
[0078] (Formula 3) B / A≦0.30
[0079] In Equation 3, A and B are the average (A) and standard deviation (B) of the content (wt%) of the doping element measured at 100 arbitrary points based on a cross section crossing the center of the negative electrode material. Specifically, A and B may be the average content (wt%, A) and standard deviation (B) of the doping element calculated from 100 arbitrary points in a line profile of the doping element crossing the center of the cross section of the negative electrode material.
[0080] More specifically, B / A in formula 3 can satisfy 0.30 or less, 0.25 or less, 0.20 or less, 0.15 or less, 0.14 or less, 0.13 or less, 0.12 or less, or 0.11 or less.
[0081] In Equation 3, B / A is a parameter that indicates the composition uniformity of the negative electrode material based on the doping element (D). The excellent composition uniformity of B / A that satisfies the above-mentioned range enables the negative electrode material to exhibit uniform mechanical and electrochemical properties.
[0082] Experimentally, the content and linear composition analysis of the doping element can be performed using, but is not limited to, an EPMA (Electron Probe Micro Analyzer) or an EDS (Energy Dispersive X-ray Spectroscopy) equipped on a transmission electron microscope or a scanning electron microscope.
[0083] In the negative electrode material for secondary batteries that satisfies the above-mentioned composition uniformity, the matrix based on elemental components can contain one or more doping elements (D) selected from the group consisting of alkali metals and alkaline earth metals, silicon (Si) and oxygen (O), and the matrix based on compound components can contain silicon oxide and a composite oxide of the doping element and silicon. Therefore, the composition uniformity of the doping element defined in formula 3 can correspond to the composition uniformity of the composite oxide, but is not necessarily limited thereto.
[0084] The negative electrode material for secondary batteries according to another embodiment (V) of the present invention includes a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of silicon oxide, alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and the volume change of the negative electrode active material layer (hereinafter, reference active material layer) having a composition of 80% by weight of active material including the negative electrode material, 10% by weight of conductive material, and 10% by weight of binder is within 60% when charged to 0.005V. In this case, the volume change (%) of the negative electrode active material layer (reference active material layer) can be defined as [thickness of reference active material layer after lithiation-thickness of reference active material layer before lithiation] / thickness of reference active material layer before lithiation*100. Experimentally, the thickness of the reference active material layer before and after lithiation can be measured by scanning electron microscope observation photographs, etc.
[0085] The volume change during charging to 0.005V is within 60%, specifically within 50%, 40%, 30%, 25%, or 20%, which means that a significantly smaller volume change occurs compared to conventional silicon-based anode materials, and this means that the main problems with conventional silicon-based anode materials are largely resolved.
[0086] The reference active material layer, which is a standard for testing the degree of volume expansion of the negative electrode material, may contain 80% by weight of the active material including the above-mentioned negative electrode material, 10% by weight of a conductive material, specifically carbon black, 10% by weight of a binder, specifically 5% by weight of carboxymethyl cellulose, and 5% by weight of styrene butadiene rubber. In this case, the active material may contain the above-mentioned negative electrode material alone or a mixture of the above-mentioned negative electrode material and a carbon-based negative electrode active material (e.g., black carbon). When the active material contains a mixture, the weight percentage of the negative electrode material may be 5% to 90% by weight based on the total weight of the mixture (100%). In the negative electrode provided with the reference active material layer (reference negative electrode), the current collector may be copper foil. Although not particularly limited, the thickness of the reference active material layer before lithiation may be 15 to 25 μm.
[0087] The charging of the reference active material layer may be performed by a charge-discharge test under the following charge-discharge cycle conditions using a half-cell (e.g., a CR2032 coin-type half-cell) having a negative electrode (reference negative electrode) provided with the reference active material layer and a metallic lithium foil as a counter electrode. The charge-discharge cycle, specifically, the first charge-discharge cycle, may be performed to 0.005 V.
[0088] Charge / discharge cycle conditions: CC / CV, cut-off voltage 0.005V~1.0V, 0.5C-rate
[0089] Unless otherwise specified below, the electrochemical characteristics (charge / discharge characteristics, discharge capacity, dQ / dV graph, etc.) of the negative electrode material including the volume change during lithiation may be the electrochemical characteristics of a half cell in which the negative electrode containing the negative electrode material and the counter electrode are metallic lithium foil, and may be the electrochemical characteristics of a half cell in which a formation process has been performed. Therefore, it goes without saying that the first cycle according to the charge / discharge cycle conditions presented when charging the reference active material layer also means the first cycle performed after the formation process has been performed. The half cell is composed of a negative electrode current collector and a negative electrode including a negative electrode active material layer that is located on at least one side of the current collector and includes the negative electrode material according to one embodiment of the present invention, a counter electrode that is metallic lithium foil, a separator interposed between the negative electrode and the counter electrode, and LiPF at a concentration of 1M in a mixed solvent in which ethylene carbonate and diethyl carbonate are mixed in a volume ratio of 1:1. 6 The electrochemical properties of the half cell may be measured at room temperature. The formation process may include a first process in which charging and discharging are performed under the conditions of CC / CV, cut-off voltage 0.005V to 1.5V, and 0.1C-rate, and a second process in which charging and discharging are performed under the conditions of CC / CV, cut-off voltage 0.005V to 1.0V, and 0.1C-rate, but it goes without saying that the present invention is not limited by the formation process conditions of the test cell (half cell), and any formation process that is normally performed in a battery used to test the electrochemical properties of a conventional anode material may be used.
[0090] According to another embodiment (VI) of the present invention, there is provided a negative electrode material for a secondary battery, which comprises a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and which is characterized in that the negative electrode material is Li in a dQ / dV graph obtained by a charge-discharge test under the following charge-discharge cycle conditions using a half cell in which a counter electrode is a metallic lithium foil: 3.75 There is a lithium insertion peak corresponding to the Si reaction, and the discharge capacity in the first charge / discharge cycle is 1200 mAh / g or more.
[0091] Charge / discharge cycle conditions: CC / CV, cut-off voltage 0.005V~1.0V, 0.5C-rate
[0092] The dQ / dV graph may be a graph showing the relationship between the differential value dQ / dV obtained by differentiating the battery capacity (discharge capacity) Q in the first charge / discharge cycle with the potential V of the metallic lithium foil reference negative electrode of the half cell and the potential V. In this case, on the dQ / dV graph, Li 3.75 The lithium insertion peak corresponding to the Si reaction may refer to a peak located in a voltage range of 0.005V to 0.100V, specifically, a voltage range of 0.005V to 0.050V, and more specifically, a voltage range of 0.005V to 0.040V.
[0093] That is, in the negative electrode material for a secondary battery according to another embodiment (VI) of the present invention, lithium is inserted into the negative electrode material. 3.5 Li exceeds Si 3.75 This means that up to Si will be performed. 3.75 The capacity of the negative electrode material can be improved by inserting lithium into Si. As a practical example, when the half cell subjected to the chemical formation process is charged and discharged under the above-mentioned charge-discharge cycle conditions, the discharge capacity (C1) in the first charge-discharge cycle can be 1200mAh / g or more, 1250mAh / g or more, 1300mAh / g or more, 1350mAh / g or more, 1400mAh / g or more, 1450mAh / g or more, or 1500mAh / g or more, and can be substantially 2500mAh / g or less.
[0094] The negative electrode material for secondary batteries according to another embodiment (VII) of the present invention includes a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of an alkali metal, an alkaline earth metal, and a post-transition metal, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix, and satisfies formula 4 during a charge-discharge test under the following charge-discharge cycle conditions using a half cell having a lithium foil as a counter electrode.
[0095] Charge / discharge cycle conditions: CC / CV, cut-off voltage 0.005V~1.0V, 0.5C-rate
[0096] (Formula 4) 95%≦C50 / C1*100
[0097] In Equation 4, C1 is the discharge capacity (mAh / g) of the negative electrode material in the first charge / discharge cycle, and C50 is the discharge capacity of the negative electrode material in the 50th charge / discharge cycle.
[0098] Specifically, C50 / C1*100 can be 95% or more, 96% or more, 97% or more, 98% or more, or 99% or more. Such cycle characteristics mean that the storage and release of lithium ions in the negative electrode material is substantially completely reversible, and that there is substantially no capacity reduction (deterioration of the negative electrode material, deterioration of the electrical contact of the negative electrode material in the negative electrode active material layer, formation of irreversible products, etc.) during repeated charge and discharge up to 50 times, and that the battery has an extremely excellent capacity retention rate.
[0099] In one embodiment, the C50 can be 1200 mAh / g or more, 1250 mAh / g or more, 1300 mAh / g or more, 1350 mAh / g or more, 1400 mAh / g or more, 1450 mAh / g or more, or 1500 mAh / g or more, and can be substantially 2500 mAh / g or less.
[0100] According to another embodiment (VIII) of the present invention, there is provided a negative electrode material for a secondary battery, comprising: a matrix containing a silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and impregnated in the matrix and having a residual compressive stress.
[0101] The residual compressive stress of the nanoparticle silicon dispersed and impregnated in the matrix, and further the stress field formed in the matrix around the silicon nanoparticles by the residual compressive stress of the silicon and the matching interface formed between the silicon nanoparticles and the matrix, can be represented as physical properties or measurable parameters of the anode material as one aspect of the anode material based on the above-mentioned Raman spectrum, another aspect of the anode material based on mechanical properties, or another aspect of the anode material based on electrochemical properties during lithiation.
[0102] In the present invention, the negative electrode material can satisfy one or more of the above-mentioned aspects (I to VIII), two or more, three or more, four or more, five or more, six or more, seven or more, or all of the aspects I to VIII.
[0103] Hereinafter, unless specifically described as being limited to "one embodiment of the present invention", the contents described below apply to all embodiments provided by the present invention.
[0104] In one embodiment, the anode material may contain one or more doping elements selected from the group consisting of silicon, oxygen, alkali metals, alkaline earth metals, and post-transition metals on an elemental basis. The silicon may include a silicon component in an elemental silicon state and a silicon component in an oxide state, and the silicon component in an oxide state may include an oxide state of silicon alone, a composite oxide state of silicon and a doping element, or all of these. The doping element may include a doping element component in an oxide state, and the doping element in an oxide state may include an oxide state of the doping element alone, a composite oxide state of silicon and a doping element, or all of these.
[0105] Based on the compound components, the anode material may contain silicon oxide, a composite oxide of a doping element and silicon, or a mixture thereof, and may also contain elemental silicon (Si). The silicon oxide is SiOx, where x can be a real number between 0.1 and 2, and the composite oxide is D l S mO n D is a doping element, l is a real number from 1 to 6, m is a real number from 0.5 to 2, and n is a real number that satisfies charge neutrality depending on the oxidation numbers of D and Si and l and m. As an example, when D is Mg, the composite oxide is MgSiO 3 and Mg 2 SiO 4 However, in the present invention, D and the composite oxide are not necessarily limited to an oxide between Mg and Mg--Si.
[0106] Based on the microstructure, the negative electrode material may contain a matrix containing silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals and alkaline earth metals, or a mixture thereof, and a dispersed phase containing silicon nanoparticles. The dispersed phase may be uniformly dispersed and impregnated within the matrix.
[0107] In one embodiment, the silicon nanoparticles can be crystalline, amorphous, or a combination of crystalline and amorphous phases, or can be substantially crystalline.
[0108] In one embodiment, the matrix may be crystalline, amorphous, or a composite phase of crystalline and amorphous. In particular, the matrix may be crystalline, or a composite phase of crystalline and amorphous. In particular, the matrix may include amorphous, crystalline, or a composite phase of amorphous and crystalline silicon oxide and a crystalline composite oxide.
[0109] The interface between the silicon nanoparticles and the matrix may include a coherent interface, an incoherent interface, or a semi-coherent interface, and may substantially include a coherent interface or a semi-coherent interface, and may more substantially include a coherent interface. As is well known, a coherent interface is an interface where the lattices of the two interfacing materials maintain lattice continuity at the interface, and a semi-coherent interface is an interface where there is a partial lattice mismatch, and such a lattice mismatch can be regarded as a defect such as a potential. Therefore, in a negative electrode material having a coherent or semi-coherent interface between the silicon nanoparticles and the matrix, the matrix region in contact with the silicon nanoparticles may be crystalline, and specifically, may be a crystalline silicon oxide, a crystalline composite oxide, or a mixture thereof. Experimentally, the interface structure of a coherent interface, an incoherent interface, or a semi-coherent interface can be determined by high-magnification scanning electron microscope observation, and this is a well-known fact to those skilled in the art.
[0110] In one embodiment, the average diameter of the silicon nanoparticles is 10 0 Nanometer order ~ 10 1 The size may be on the order of nanometers, specifically, 1 to 50 nm, 2 to 40 nm, 2 to 35 nm, 2 to 30 nm, 2 to 20 nm, or 2 to 15 nm, but is not limited thereto. However, silicon nanoparticles of a level of 30 nm or less may be advantageous in that they form a coherent interface with the matrix as a whole, and stress is formed in a wider region of the matrix due to the compressive stress remaining in the silicon nanoparticles. Experimentally, the average diameter of silicon nanoparticles may be calculated by measuring the size of silicon nanoparticles in the negative electrode material using a transmission electron microscope observation image, and averaging the sizes measured for 10 or more, 20 or more, or 30 or more silicon nanoparticles.
[0111] In one embodiment, the doping element may be one or more selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), indium (In), tin (Sn), and bismuth (Bi). Thus, the composite oxide may be an oxide between silicon and one or more elements selected from lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), aluminum (Al), gallium (Ga), indium (In), tin (Sn), and bismuth (Bi). The mechanical and electrochemical properties of the negative electrode material can be further improved by the synergistic effect between the composite oxide and the silicon nanoparticles having residual compressive stress. In order to be advantageous in forming a matching interface with the silicon nanoparticles, the doping element can be one or more elements selected from the group consisting of alkali metals and alkaline earth metals, specifically lithium (Li), sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba), and more preferably, can be one or more elements selected from alkaline earth metals, specifically magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba). Most preferably, in terms of easy formation of a matching interface and synergistic effect with the silicon nanoparticles having residual compressive stress, the doping element can include magnesium. As described above, the doping element may be contained in the negative electrode material in the form of a complex oxide with silicon and / or in the form of an oxide of the doping element, and may be contained in the negative electrode material mainly in the form of a complex oxide. Specifically, when the matrix contains the doping element in the form of a complex oxide with silicon, the complex oxide may include a crystalline substance, and more substantially, the complex oxide may be crystalline. This allows the matrix to contain a crystalline complex oxide.
[0112] In one embodiment, the silicon oxide contained in the matrix may be SiOx, where x is a real number between 0.1 and 2, more specifically, a real number between 0.5 and 2, and may include a first silicon oxide and a second silicon oxide having different x. As a practical example, the silicon oxide contained in the matrix may be SiO x1 (x1 is a real number between 1.8 and 2) x2 (x2 is a real number of 0.8 to 1.2) The silicon oxide contained in the matrix may be crystalline, amorphous, or a composite phase of crystalline and amorphous, or may be substantially amorphous.
[0113] In one embodiment, the anode material may contain 15-50% by weight of nanoparticulate silicon and the remainder matrix.
[0114] In one specific example, the matrix of the negative electrode material can contain both silicon oxide and composite oxide, and the matrix can satisfy A / B of 2 to 50, 2 to 40, 2 to 30, or 2 to 20, where A is the part by weight of the composite oxide relative to 100 parts by weight of silicon oxide, and B is the concentration of the doping element based on weight percent in the negative electrode material.
[0115] In one embodiment, the anode material can be in particulate form. The particulate anode material can have a particle size typically desired for secondary battery applications, for example, 10 0 μm order ~ 10 1 The average diameter may be on the order of μm, specifically, 5 μm to 30 μm, but is not limited thereto.
[0116] In one embodiment, the negative electrode material may further include a coating layer containing carbon, specifically a surface coating layer coated on the surface of the negative electrode material. Such a surface coating layer can advantageously improve the electrical properties of the negative electrode material. The thickness of the coating layer may be on the order of 2 to 30 nm, but is not necessarily limited thereto.
[0117] In one embodiment, the anode material contains silicon nanoparticles having residual compressive stress, and when electrochemically alloyed with lithium (lithiation), can have an alloying ratio of 3.5 (or more) to 3.75 moles of lithium per mole of silicon, specifically 3.6 to 3.75 moles. Such a high alloying ratio is highly advantageous for high capacity. In one embodiment, the anode material can have high initial charge / discharge efficiency and capacity retention characteristics.
[0118] The present invention includes an anode containing the above-mentioned anode material. The anode can be a secondary battery, specifically a lithium secondary battery anode. The anode can include a current collector and an anode active material layer located on at least one side of the current collector and containing the above-mentioned anode material. The anode active material layer can further include the anode material and a binder and a conductive material typically used in secondary battery anodes, as necessary.
[0119] The present invention includes a secondary battery including the above-mentioned negative electrode. Specifically, the present invention includes a lithium secondary battery including the above-mentioned negative electrode. The lithium secondary battery can include a positive electrode including a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector, the above-mentioned negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte that conducts lithium ions. The positive electrode current collector, the negative electrode current collector, the positive electrode active material and composition of the positive electrode active material layer, the separator and the electrolyte solvent, the insulating film, or the concentration of the electrolyte salt may be materials and compositions that are usually adopted in lithium secondary batteries.
[0120] (Example) Si, SiO 2 The raw materials for MgO were 6(Si):4.5(SiO2 ):1.5 (MgO) was put into a powder mixer and mixed homogeneously to produce the raw material.
[0121] The raw material was filled in a crucible in a vacuum chamber of 0.1 torr or less, weighing 26 kg, and then heated at 1,400° C. to vaporize it, and then condensed on a collection plate at 400° C. to obtain magnesium-doped silicon oxide.
[0122] The obtained magnesium-doped silicon oxide was heat-treated at 900° C. in an Ar atmosphere for 15 hours to prepare a bulk negative electrode material for secondary batteries.
[0123] The produced bulk-type secondary battery anode material was mechanically pulverized to an average particle size of 5 μm to produce particulate anode material, and the particulate anode material was coated with 5 wt % carbon through a CVD process at 850°C using hydrocarbon gas to produce carbon-coated anode material powder.
[0124] Comparative Example 1 Si, SiO 2 The raw materials for MgO were 6(Si):4.5(SiO 2 ):1.5 (MgO) was put into a powder mixer and mixed homogeneously to produce the raw material.
[0125] The raw material was filled in a crucible in a vacuum chamber of 0.1 torr or less, weighing 26 kg, and then heated to 1,400°C to vaporize it, and then condensed on a collection plate at 400°C to obtain magnesium-doped silicon oxide. The obtained magnesium-doped silicon oxide (anode material for bulk-type secondary batteries) was mechanically pulverized to an average particle size of 5μm to produce particulate anode material, and the particulate anode material was coated with 5% by weight of carbon through a CVD process at 850°C using hydrocarbon gas to produce carbon-coated anode material powder.
[0126] Comparative Example 2 Si and SiO 224 kg of the mixed raw material was placed in crucible A, and 2 kg of metallic Mg was placed in crucible B. Crucible A was heated to 1,500°C, and crucible B was heated to 900°C to vaporize the material, which was then condensed on a collection plate at 900°C to obtain magnesium-doped silicon oxide.
[0127] The obtained magnesium-doped silicon oxide (anode material for bulk-type secondary batteries) was mechanically pulverized to an average particle size of 5 μm to produce a particulate anode material, and the particulate anode material was coated with 5 wt % carbon through a CVD process at 850°C using hydrocarbon gas to produce a carbon-coated anode material powder.
[0128] -Experimental example ·Mg content deviation Based on a cross section crossing the center of the magnesium-doped silicon oxide before pulverization (Comparative Example 2) and the bulk-type secondary battery negative electrode material obtained by heat treatment (Example), the average content (wt%) of the doping element calculated by measuring 100 arbitrary points in the linear composition crossing the center of the cross section using EDS (Electron Disperse Spectroscopy) was calculated as A and the standard deviation of the content was calculated as B, which are shown in Figure 1. As a result of the composition analysis, the B / A of the negative electrode material sample prepared in the Example was 0.1, and in the case of Comparative Example 2, the B / A was 0.43.
[0129] Raman analysis After grinding, the anode material was analyzed using μ-Raman (equipment name: XperRam c, Nanobase, Korea) under the following conditions based on the Raman signal of silicon. The Raman signal of the anode material powder is shown in FIG. 2. As shown in FIG. 2, the silicon Raman signal (peak center) of the anode material manufactured in the embodiment is 523.6 cm -1 It is found that the negative electrode material produced in the comparative example has residual compressive stress, and the negative electrode material produced in the comparative example has residual tensile stress. In addition, the FWHM of the silicon Raman signal produced in the example was measured, and the FWHM was 12 cm. -1 It was confirmed that this is larger than the FWHM of the single crystal silicon Raman signal (C-Si(ref) in the figure).
[0130] Analysis conditions: Excitation laser wavelength 532 nm, laser power 0.5 mW, spectrometer resolution 1 cm -1 , 1g of powdered negative electrode material, detector exposure time 15s
[0131] The residual stress in silicon was calculated using the Raman measurement results and the following formula, and the silicon residual stress in the particulate negative electrode material and the silicon residual stress in the bulk negative electrode material were summarized in Table 1. As summarized in Table 1 together with the results of the comparative examples, in the case of the negative electrode materials manufactured in the examples, it can be seen that the silicon has a residual compressive stress of 0.7 GPa in bulk form and a residual compressive stress of 0.25 GPa in particulate form, and that in the case of Comparative Example 1, the Si in the amorphous phase and in the case of Comparative Example 2, the Si have tensile stress rather than compressive stress.
[0132]
number
[0133] where σ is the residual stress, Δω is the Raman signal of single crystal silicon (c-Si(ref) in the figure, 520.4 cm -1 ) the difference in the Raman signal of the sample measured relative to the measured silicon Raman signal wavenumber (=measured silicon Raman signal wavenumber-single crystal silicon Raman signal wavenumber), where σ is a positive value for compressive stress and a negative value for tensile stress.
[0134] A μ-Raman analysis (equipment name: XperRam c, Nanobase, Korea) of magnesium-doped silicon oxide before grinding (comparative example) and bulk-type secondary battery anode material obtained by heat treatment (example) was performed under the following conditions to perform a two-dimensional mapping analysis based on the Raman signal of silicon. The mapping results are shown in Figure 3. In the case of the anode material produced in the example, the Raman peak of silicon was detected in all pixels, and the shift for each pixel = WN i As a result of measuring (Si)-WN(ref), it was confirmed that the deviation range was 2.86 (minimum value) to 4.58 (maximum value).
[0135] Mapping conditions: excitation laser wavelength = 532 nm, laser power = 0.1 mW, detector exposure time (exposure time per unit analysis area) 1 sec, focal length = 30 mm, grating = 1800 grooves / mm, pixel resolution = 1 cm -1 , mapping size = 14 μm × 14 μm
[0136] ·Mechanical properties The particle strength and particle expansion were measured using a Shimadzu MCT-W microcompression tester. The particle strength was measured for 10 random particles with a diameter of 10 μm, and the measurement results are summarized in Table 1.
[0137] The micro compression tester continuously applies force to the particles, and the pressure at which the particles break is defined as the particle strength, which is automatically measured.
[0138] A nanoindentation tester (Anton Paar, Austria) was used to test the cross-sections of the magnesium-doped silicon oxide (Comparative Example 1) before pulverization and the bulk-type secondary battery negative electrode material (Example) obtained by heat treatment. The nanoindentation test (indenter) conformed to the measurement standard of ISO 14577-1 E, and the measurement conditions were a Berkovich indenter, a Poisson's ratio of 0.3, a maximum load of 50 mN, and a load application rate of 100 mN / min. In this case, the separation distance between the indentation marks by the indenter was at least 10 μm or more, and the test was performed in a matrix form of 5 × 5 to 25 × 25, and the strength and elastic modulus calculated from this are shown in FIG. 4.
[0139] Battery manufacturing The final negative electrode powder was used as the active material, and the active material:conductive material (carbon black):CMC (Carboxymethyl cellulose):SBR (Styrene Butadiene Rubber) were mixed in a weight ratio of 8:1:0.5:0.5, and a solvent was added to produce an active material slurry, which was then applied to a copper foil with a thickness of 17 μm and dried at 90°C for 40 minutes. After drying, a 14 mm diameter was punched out, and a 16 mm diameter metallic lithium was used as the counter electrode, sandwiched between an 18 mm diameter separator, and filled with electrolyte to produce a CR2032 coin-type half cell. The electrolyte was a 1M LiPF in a solvent of EC (Ethylene carbonate) / DEC (Diethyl carbonate) mixed in a volume ratio of 1:1. 6 was dissolved, and 3wt% of FEC (fluoroethylene carbonate) was used as an additive. The formation process was performed by charging the manufactured battery to 0.005V at a constant current of 0.1C (lithiation), charging at a constant voltage of 0.005V until it reached 0.01C, discharging at a constant current of 0.1C to 1.5V (de-lithiation) (first formation step), charging again at a constant current of 0.1C to 0.005V, charging at a constant voltage of 0.005V until it reached 0.01C, and discharging at a constant current of 0.1C to 1.0V (de-lithiation) (second formation step).
[0140] Battery performance evaluation Charge-discharge cycle conditions: charge (lithiation) at a constant current of 0.5C to 0.005V, charge at a constant voltage of 0.005V until it reached 0.05C, and then discharge (de-lithiation) at a constant current of 0.5C to 1.0V. Number of charge / discharge cycles: 50 times
[0141] The discharge capacity of the first charge / discharge cycle is shown in Table 1, along with the initial efficiency based on the charge / discharge in the first chemical step and the capacity retention rate of C50 / C1*100, and a graph showing the charge and discharge capacities in the first chemical step, the second chemical step, and the charge / discharge cycle is shown in Figure 5.
[0142] [Table 1]
[0143] Figure 6 is a high-magnification transmission electron microscope photograph of the negative electrode material prepared in the example, and as can be seen from Figure 6, the average diameter of the crystalline silicon nanoparticles is about 6.7 nm, and Figure 7 is a high-magnification transmission electron microscope photograph of the matrix and a selected area diffraction pattern (SADP) of the area circled in yellow is inserted at the top. As a result of the HR-TEM and SADP analysis of Figures 6 and 7, it was confirmed that the matrix contains crystalline magnesium silicate and that the silicon nanoparticles form a coherent interface with the crystalline magnesium silicate.
[0144] Figure 8 shows scanning electron microscope images of the cross section and thickness of the anode before lithiation and the cross section and thickness of the anode after lithiation at 0.005 V in the third charge / discharge cycle (the first charge / discharge cycle in the life evaluation stage). It was confirmed that the volume expansion rate due to the change in thickness before and after lithiation was only 15%.
[0145] FIG. 9 shows the particle size distribution of the crushed and carbon-coated negative electrode powder. 50 ) It can be seen that the particle size is 8.3 μm.
[0146] FIG. 10 shows the dQ / dV graph for the first charge / discharge cycle. As can be seen from FIG. 10, Li 3.75 It can be seen that there is a lithium insertion peak corresponding to the Si reaction. This shows that the lithium ion of the negative electrode material prepared in the example is carried out at an alloying ratio of 3.75 moles of lithium per mole of silicon.
[0147] Figure 11 shows the selected area diffraction pattern (SADP) of the negative electrode material charged to 0.005 V in the first charge-discharge cycle, which was observed under a transmission electron microscope and selectively analyzed only the lithiated silicon nanoparticles. 3.75 It can be directly confirmed that the Si reaction occurs, which is consistent with the dQ / dV graph results in FIG.
[0148] The present invention has been described above with reference to specific and limited examples and drawings, but these are provided to facilitate a more general understanding of the present invention. The present invention is not limited to the above examples, and various modifications and variations are possible from such descriptions by those having ordinary knowledge in the field to which the present invention pertains.
[0149] Therefore, the concept of the present invention should not be limited to the above-described embodiments, and all things equivalent to or equivalent modifications of the claims described below, as well as the concept of the present invention, fall within the scope of the invention.
Claims
1. A negative electrode material for secondary batteries comprising: a matrix containing a composite oxide of silicon and one or more doping elements selected from the group consisting of silicon oxide, alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof; and silicon nanoparticles dispersed and impregnated in the matrix and having residual compressive stress, the negative electrode material having a hardness of 4.0 GPa or more and a Young's modulus of 40 MPa or more as measured by a nanoindentation test.
2. A negative electrode material for secondary batteries, comprising a matrix containing a silicon oxide, a composite oxide of silicon and one or more doping elements selected from the group consisting of alkali metals, alkaline earth metals, and post-transition metals, or a mixture thereof, and silicon nanoparticles dispersed and impregnated in the matrix and having residual compressive stress, the particles having a compressive strength of 100 MPa or more.
Citation Information
Patent Citations
Negative electrode material for secondary battery, and its manufacturing method
JP2010170943A
Negative electrode material for nonaqueous secondary battery and method for producing the material, and lithium ion secondary battery
JP2011222151A
Negative electrode material for non-aqueous electrolyte secondary battery, method for producing the same, and non-aqueous electrolyte secondary battery including the same
JP2018519648A
Negative electrode active material, negative electrode containing the same, and lithium secondary battery
JP2020529709A
Anode active material, anode including the anode active material, and lithium secondary battery including the anode
KR1020150045336A